A Rapid Evolving microRNA Cluster Rewires Its Target Regulatory Networks in Drosophila - Lyu, Yang; Liufu, Zhongqi; Xiao, Juan; Tang, Tian (Frontiers in Genetics, 2021)
New miRNAs are evolutionarily important but their functional evolution remains unclear. Here we report that the evolution of a microRNA cluster, mir-972C rewires its downstream regulatory networks in Drosophila. Genomic analysis reveals that mir-972C originated in the common ancestor of Drosophila where it comprises six old miRNAs. It has subsequently recruited six new members in the melanogaster subgroup after evolving for at least 50 million years. Both the young and the old mir-972C members evolved rapidly in seed and non-seed regions. Combining target prediction and cell transfection experiments, we found that the seed and non-seed changes in individual mir-972C members cause extensive target divergence among D. melanogaster, D. simulans, and D. virilis, consistent with the functional evolution of mir-972C reported recently. Intriguingly, the target pool of the cluster as a whole remains relatively conserved. Our results suggest that clustering of young and old miRNAs broadens the target repertoires by acquiring new targets without losing many old ones. This may facilitate the establishment of new miRNAs in the existing regulatory networks.